78.3k views
2 votes
Given the function f(x) = 6x2 −13, what is f(-3)? A. -67 B. -4 C. 41 D. 311

2 Answers

4 votes

Answer:

-4

Explanation:

Please write f(x) as 6x^2 - 13; " ^ " indicates exponentiation.

With f(x) = 6x^2 - 13, we substitute -3 for x in both instances:

f(-3) =(-3)^2 - 13 = 9 - 13 = -4

User KOssi
by
4.9k points
5 votes

Answer: C. 41

Explanation:

The quadratic function is:


f(x) = 6x^2-13

Then, to find
f(-3) you need to substitute the input value
x=-3 into the quadratic function, to obtain the corresponding output value.

Then, when
x=-3 the output value is:


f(x) = 6x^2-13


f(-3) = 6(-3)^2-13


f(-3) = 6(9)-13


f(-3) = 41

This matches with the option C.

User Alexander Dunaev
by
4.4k points